Advances in pathophysiology and neuroimaging: Implications for sleep and dementia. Issue 6 (14th November 2019) - Ward, Stephanie A.; Pase, Matthew P.
ABSTRACT: The burden of dementia is increasing globally. In the absence of curative treatment, preventive strategies to delay or reduce progression of dementia are crucial. This relies on the identification of modifiable risk factors. The effects of dementia on sleep are well recognized; however, there is now growing evidence suggesting a bidirectional relationship between sleep pathologies and dementia. SDB, poor quality sleep and extremes of sleep duration are commonly experienced by both middle‐aged and older populations. All have been associated with increased risk of dementia and cognitive decline in a number of observational studies, albeit inconsistently. The mechanisms by which these sleep disorders may contribute to neurodegeneration are manifold, and include impacts of fragmented sleep on the clearance of neurotoxins, and in SDB by the additive effects of intermittent hypoxia on beta‐amyloid production, hypoxic cell death, neuroinflammation and damage to cerebral vasculature. Untangling the mechanisms by which sleep pathologies may impact risk of dementia is a challenge. Many insights into the pathophysiology of these relationships have been derived from animal‐ and population‐based studies. Neuroimaging modalities offer important opportunities to further understand the link between sleep pathologies and dementia risk in vivo, especially in the critical preclinical phase of AD. In this review, we canvas updates in dementia pathophysiology, the evidence linking sleep pathologies with dementia and outline the advances in determining this potential pathophysiological link that have eventuated from the application of neuroimaging. Abstract : Find the whole series here